Further insight into the mechanism of heavy metals partitioning in stormwater runoff - Djukić, Aleksandar; Lekić, Branislava; Rajaković-Ognjanović, Vladana; Veljović, Djordje; Vulić, Tatjana; Djolić, Maja; Naunovic, Zorana; Despotović, Jovan; Prodanović, Dušan (Journal of environmental management, 2016)
Various particles and materials, including pollutants, deposited on urban surfaces are washed off by stormwater runoff during rain events. The interactions between the solid and dissolved compounds in stormwater runoff are phenomena of importance for the selection and improvement of optimal stormwater management practices aimed at minimizing pollutant input to receiving waters. The objective of this research was to further investigate the mechanisms responsible for the partitioning of heavy metals (HM) between the solid and liquid phases in urban stormwater runoff. The research involved the collection of samples from urban asphalt surfaces, chemical characterization of the bulk liquid samples, solids separation, particle size distribution fractionation and chemical and physico-chemical characterization of the solid phase particles. The results revealed that a negligible fraction of HM was present in the liquid phase (less than 3% by weight), while there was a strong correlation between the total content of heavy metals and total suspended solids. Examinations of surface morphology and mineralogy revealed that the solid phase particles consist predominantly of natural macroporous materials: alpha quartz (80%), magnetite (11.4%) and silicon diphosphate (8.9%). These materials have a low surface area and do not have significant adsorptive capacity. These materials have a low surface area and do not have significant adsorptive capacity. The presence of HM on the surface of solid particles was not confirmed by scanning electron microscopy and energy dispersive X-ray microanalyses. These findings, along with the results of the liquid phase sample characterization, indicate that the partitioning of HM between the liquid and solid phases in the analyzed samples may be attributed to precipitation processes. •Strong correlation between HM and TSS was confirmed in samples of urban runoff.•Examined urban runoff solids consist of macroporous materials only.•Examined urban runoff solids are unsuitable for an effective adsorption process.•Presence of HM on the surface of urban runoff solids was not detected by EDS analyses.•HM partitioning in urban runoff may be attributed to precipitation processes.